(untitled) (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
With the advancement of modern science, technology, and biological development, the use of medications has increased, and in some cases, due to uncontrolled usage by parents, children are often exposed to drug poisoning. This poses serious health and life-threatening risks to children, depending on their age, body characteristics, and the type of medication used, as evidenced by international studies. The analysis of the medical history of children poisoned by drugs and chemicals aims to identify the causes of poisoning, the medications and chemicals involved, treatment costs, and preventive measures. Мethods: The study will be conducted аs a retrospective observation study based on the medical record inpatients in the Internal Medicine Department of National Center for Maternal and Child Health. A sampling approach will be used, nd the data will be analyzed using both extensive indicators and clarification techniques.; Results: The results of the study showed that the majority of poisoning cases involving by drugs and chemicals were accidental (73.24%). Analysis of age distribution of the children affected by poisoning, the highest number of cases were found in young children and preschool-aged children (61.04%). Among adolescents, there was a tendency for self-harm (16.74%) and drug/chemical use for recreational purposes (1.65%). The most common form of poisoning was due to medications, with carbamazepine, iron preparations, and nafazoline being the most frequently involved drugs; Conclusions: The study confirms that young children are most frequently affected by acute poisoning from drugs and chemicals. Accordingly, there is a need to enhance oversight and create conditions for the safe storage of chemicals and pharmaceutical substances. Additionally, providing psychological support services for adolescents, developing content and educational programs to positive behaviors, which may help reduce the risk of self-harm and substance abuse.